Efektivitas Penggunaan Bahasa Jawa Dalam Promosi Kesehatan Gigi Dan Mulut Untuk Menurunkan Skor Plak Gigi Pada Anak Usia 6-8 Tahun Di Mim Klaseman Gatak Sukoharjo - Sulistiono, Tri, drg. Lasmi Dewi Nurnaini, Sp.KGA (2016)
Health promotion is one of the government's efforts to overcome health problems in Indonesia. Health promotion do to increase the ability of society through from, by, for and together with society, so that they can help themselves, as well as develop activities resourceful from society, based on local culture and support by public policy that has a vision of health. Communication is a must have competency in health promotion. Language required in communication to convey the message. Examples of the language used in the communication is socio cultural language. Communication with the socio cultural language is often occur, because there are interactions between the people in the same culture. Javanese language was socio cultural language that born from Javanese. Ngoko lugu in Javanese language is one of the levels commonly used in communicate with someone who is already familiar, or to someone whose lower status. This study aimed was to determine the effectiveness of using javanese languange in promotion of oral health to reduce plaque score for children age 6-8 years in MIM Klaseman Gatak Sukoharjo. This study was quasi experimental research design with pretest posttest group design. Subjects were divided into two groups which was the Javanese language as the treatment group and Indonesian language as the control group. Measurements plaque scores in this study using PHP-M. This study was conducted over seven days. The effectiveness of oral health promotion in decreasing plaque scores were seen based on the difference between pretest and posttest scores for each group. Data were analyzed using independent t-test. The results showed that the mean of difference in plaque score on Javanese language groups was 17.23 and 10.41 on Indonesian group. The data of difference of plaque scores were then tested using Independent t test and showed p = 0.002 (p <0.05) , so it can be concluded that the promotion of oral health in the group that used Javanese language was more effective in reducing plaque score than Indonesian language group.